2010
DOI: 10.1088/0031-9155/55/18/001
|View full text |Cite
|
Sign up to set email alerts
|

The impact of standing wave effects on transcranial focused ultrasound disruption of the blood–brain barrier in a rat model

Abstract: Microbubble mediated disruption of the blood brain barrier (BBB) for targeted drug delivery using focused ultrasound shows great potential as a therapy for a wide range of brain disorders. This technique is currently at the pre-clinical stage and important work is being conducted in animal models. Measurements of standing waves in ex vivo rat skulls were conducted using an optical hydrophone and a geometry dependence was identified. Standing waves could not be eliminated through the use of swept frequencies, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
86
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(91 citation statements)
references
References 27 publications
5
86
0
Order By: Relevance
“…Also, it has been shown that standing waves were not necessary in the BBB opening mechanism. 43,44 Therefore, the standing wave effect in this study was deemed insignificant.…”
Section: Discussionmentioning
confidence: 88%
“…Also, it has been shown that standing waves were not necessary in the BBB opening mechanism. 43,44 Therefore, the standing wave effect in this study was deemed insignificant.…”
Section: Discussionmentioning
confidence: 88%
“…Preclinical investigation in this frequency range is important because the acoustic behavior of microbubbles and corresponding bioeffects may vary as a function of FUS frequency (23,37). However, such a low frequency is not typically adopted in rodent experiments due to the elongated focal area that exceeds the thickness of a rat brain, leading to internal reflections and standing waves (38). We therefore combined two spherically curved transducers to double the effective aperture size and provide significantly improved focusing in the axial direction.…”
Section: Discussionmentioning
confidence: 99%
“…The variability in the DOX measurements in the hippocampus could have been due to noisy data induced by autofluorescence. DOX fluorescence (excitation/emission: 480/575 nm 38 ) overlapped with the yellow/green autofluorescence of tissue. A two-wavelength excitation approach (see SI Methods for details) was thus applied in DOX imaging to remove the autofluorescence.…”
Section: Controlling the Chemotherapeutic Drug Delivery In F98 Rat Glmentioning
confidence: 99%
“…The energy therefore has more room to generate complicated interference inside the cavity, and standing wave problems are a serious concern. In small animal cranial cavities, standing waves can be induced by a wide range of frequencies (0.26-2.5 MHz) when the cavity size is larger (i.e., within a few wavelength of the ultrasound wavelength) (29). Previous studies using a phantom similar in size to the human cranium showed that 28-kHz ultrasound produced a standing wave caused by constructive interference at the depth of its wavelength (i.e., $55 mm off the interface).…”
Section: Discussionmentioning
confidence: 99%